I love you madly : Marie-Antoinette and Count Fersen - the secret letters /: Marie-Antoinette and Count Fersen - the secret letters. (2016) - Queen, consort of Louis XVI, King of France, Marie Antoinette, 1755-1793; greve, Fersen, Hans Axel von, 1755-1810
No abstract available